Opportunities, Limitations and Gaps in the Ecological Restoration of Drylands in Argentina - Busso, C A; Perez, D R (Annals of Arid Zone, 2019)
This paper reviews the opportunity to ecologically restore, impaired drylandecosystems in Argentina. This is very important because they contribute to (1) control theeffects of desertification in the country, and (2) reverse the complex social consequencesof the degradation. Reported benefits and limitations, as well as gaps, in the ecologicalrestoration of drylands in Argentina, where more than 67% of continental lands arearid and semi-arid territories are affected by abusive (and inadequate) utilization arediscussed. The selected restoration case studies on drylands in the country were groupedinto: (1) prescribed natural regeneration, and (2) assisted natural regeneration, partialreconstruction and (3) complete restoration. Based on comparison of results from otherdrylands of the world there may be possibilities of applying some practices to fill theecological gaps. Finally, there is an analysis of costs and benefits, monitoring proceduresand potential for application of useful new techniques as levels of intervention areincreased.Key words: Branching, direct seeding, natural regeneration, plantation, topsoil.